Spending on Intangibles and The Growth of Public Sector Enterprises In India: A Measure-Specific DEA Analysis - Choudhury, Mrinal; Roy, Chinmoy (International Journal of Cultural and Social Science, 2024)
A recent surge of intangible investment to navigatethe productive capability of Central Public Sector Enterprises (CPSEs) resurrected a range of doubt about the trajectory of choices and the actual managerial space that actualizes these choices. Though spending on intangibles and more particularly on R&D contribute substantially to growth parameters but the ambiguous magnitude of spending patterns and treatment of such expenditure from regular business operation to an investment element, in particular, to enhance the valued capability, yet unresolved in the corporate world. Recent studies on the usefulness of intangibleoutlay and capitalization of the same in improving future returns evidenced a gloomy pattern of crisis in the measurement and allocation of intangibles. As evidenced, most of the spending on intangibles by the business units in India is targeted to secure “patent for profit” rather than to achieve “valued capability” to expand real opportunities to choose between alternatives. Based on the last ten years' dataset of Maharatna Enterprises this study critically examines the contribution of decisive one from the container of four inputs namely spending on software, other R&D expenditure, materials, and employee costs on a set of productive activities covering the revenue and net- value- added, as these are more regular in enhancing both profit and production capability with the help of input-oriented VRS weighted measure-specific DEA model. Results show that the multidimensional performances between the enterprises are not uniform throughout the study period and that the efficiency is highly correlated with the size of a few companies like ONGC, BHEL, and GALE and higher spending DMUs on intangibles do not necessarily have higher-ranked performance in terms of returns and net value added. This study provides valuable insights for managers aiming to maximize the benefit of variety in Software and other R&D spending patterns considering the sizes of the companies while minimizing the risk associated with excessive diversity beyond the moderate threshold in intangible investments.